Microstructural characterization of materials - Brandon, D. G. (Quantitative software engineering series, 2008)
Microstructural Characterization of Materials, 2nd Edition is an introduction to the expertise involved in assessing the microstructure of engineering materials and to the experimental methods used for this purpose. Similar to the first edition, this 2nd edition explores the methodology of materials characterization under the three headings of crystal structure, microstructural morphology, and microanalysis. The principal methods of characterization, including diffraction analysis, optical microscopy, electron microscopy, and chemical microanalytical techniques are treated both qualitatively and quantitatively. An additional chapter has been added to the new edition to cover surface probe microscopy, and there are new sections on digital image recording and analysis, orientation imaging microscopy, focused ion-beam instruments, atom-probe microscopy, and 3-D image reconstruction. As well as being fully updated, this second edition also includes revised and expanded examples and exercises, with a solutions manual available at http://develop.wiley.co.uk/microstructural2e/